Britain and the Arab-Israel Conflict: Questioning the Motives Behind Continued Aid to 1967 Palestinian Refugees - Bin Zakariah, Muhamad Hasrul (Journal of Islam in Asia (E-ISSN 2289-8077), 2008)
British involvement in Middle East politics can be traced to long before the First World War when its economic and strategic interests appeared to be the main reason for the involvement. The emergence of the newly created Israeli state, following the Balfour Declaration, marked the beginning of the Palestinian refugee crisis. Between 1948 and 1956, historical liability and obligation forced the British to be involved in providing humanitarian aid to the Palestinian refugees. British involvement in the Suez Crisis later in 1956, was a tragedy for British influence in the Middle East. Many scholars concluded that the 1956 campaign marked “the end of British empire in the Middle East” and the beginning of the cold war, American-Soviet rivalry that left Britain marginalised. Even prominent Middle East scholars such as Michael Ben Oren, in his book Six Days of War: June 1967 and the Making of Modern Middle East, did not give attention to the British role and involvement in the 1967 crisis. However, the British efforts to regain Arab trust whilst preserving its economic and strategic interests in the Middle East persuaded Britain to remain involved with the Palestinian refugee crisis. None of these scholars have tried to analyse the motives behind continued British involvement in humanitarian aid for Palestinian refugees – the crisis which lingers long after the end of the British Empire in the Middle East. This paper discusses this topic with a focus on refugees from the 1967 war and attempts to explain the reasons for continuation of British aid from an historical perspective. This research was based on historical document analysis and the extraction of archival sources from The National Archive (TNA) in London.